Role Congruity Theory and Women in Leadership: A Cross-sectional Qualitative Study Describing the Challenges Faced by Women Achieving Leadership Positions in Medium Sized Organisations within KZN - Read, Caitlyn Cassidy (The IIE, 2018)
Understanding and overcoming the challenges behind the success of female leaders is important for the effective performance of female leaders. It has been found that a distressed journey to leadership can impact on how a female performs and is treated in her senior role. There are very few females in leadership positions as they are not afforded the opportunity to showcase their potential and succeed as a result of the entrenched patriarchal system in South Africa. This erodes their self-confidence to work towards achieving try and achieve senior roles, which poses a major problem. In response to this status quo, a study was undertaken to describe the common challenges female leaders faced during their journey to becoming a leader and to provide recommendations for aspiring female leaders on how to overcome the challenges. To facilitate this, the Role Congruity Theory was utilised. The qualitative and descriptive nature of the study required a set of in-depth interviews as the approach to obtain an information rich analysis of the challenges from the female participants who were selected through purposive sampling based on their position within the organisation. This research considers the glass-ceiling affect and analyses how this impacts on certain aspects of female leadership roles. Therefore, this research created a thematic foundation to interpret findings effectively in order for these to be trustworthy. The findings included female who are leaders in KwaZulu-Natal, who are not affected by the glass-ceiling, but rather through stereotypes that have made them doubt their capabilities.
Keywords: female leadership; female work performance; patriarchal system; Role Congruity Theory; medium sized organisations